PELATIHAN PEMBUATAN PEWARNA BATIK ALAMI MENGGUNAKAN MESIN PENGADUK MULTIFUNGSI UNTUK UMKM di BEKASI - Cahyati, Sally; Astuti, Pudji; Azmi, Nora; Hadisoebroto, Rositayanti; Putri, Larasati Rizky (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2023)
Indonesia is the largest batik-producing country in the world. The batik industry is growing rapidly in Indonesia, apart from having a positive impact, there is also a negative impact, namely environmental pollution in waterways and groundwater sources due to liquid waste resulting from batik production. This colored and smelly waste can cause allergies and damage the quality of groundwater which is also a source of drinking water for the surrounding community. Apart from treating wastewater using IPAL, another solution is for batik craftsmen to be motivated and raise awareness to use natural, environmentally friendly dyes. This is what prompted the PKM activity "Training on Making Natural Batik Dye Using a Multifunctional Mixer Machine for Bekasi Batik MSMEs". In terms of quality, batik with natural dyes has a higher value than batik using synthetic dyes. Economically, there is still a large market for environmentally friendly batik, especially from customers who are environmentally conscious both at home and abroad. The method for making natural dyes, which used to be boiled using just a pan, will be improved by using a multi-function stirring machine, making it more productive, efficient, and hygienic so that natural dyes are not easily damaged. The manufacturing process time can also be shorter so that the overall production time is not disrupted. Increasing the awareness and ability of craftsmen in processing natural dyes is expected to also improve the quality of batik products and the environment around the production site. In the end, it is hoped that an increase in craftsmen's business will occur